Overexpression of mitochondrial uncoupling protein 1 (UCP1) induces a hypoxic response in Nicotiana tabacum leaves - Barreto, Pedro; Okura, Vagner; Pena, Izabella A.; Maia, Renato; Maia, Ivan G. [UNESP]; Arruda, Paulo (Oxford University Press on behalf of the Society for Experimental Biology., 2015)
Mitochondrial uncoupling protein 1 (UCP1) decreases reactive oxygen species production under stress conditions by uncoupling the electrochemical gradient from ATP synthesis. This study combined transcriptome profiling with experimentally induced hypoxia to mechanistically dissect the impact of Arabidopsis thaliana UCP1 (AtUCP1) overexpression in tobacco. Transcriptomic analysis of AtUCP1-overexpressing (P07) and wild-type (WT) plants was carried out using RNA sequencing. Metabolite and carbohydrate profiling of hypoxia-treated plants was performed using (1)H-nuclear magnetic resonance spectroscopy and high-performance anion-exchange chromatography with pulsed amperometric detection. The transcriptome of P07 plants revealed a broad induction of stress-responsive genes that were not strictly related to the mitochondrial antioxidant machinery, suggesting that overexpression of AtUCP1 imposes a strong stress response within the cell. In addition, transcripts that mapped into carbon fixation and energy expenditure pathways were broadly altered. It was found that metabolite markers of hypoxic adaptation, such as alanine and tricarboxylic acid intermediates, accumulated in P07 plants under control conditions at similar rates to WT plants under hypoxia. These findings indicate that constitutive overexpression of AtUCP1 induces a hypoxic response. The metabolites that accumulated in P07 plants are believed to be important in signalling for an improvement in carbon assimilation and induction of a hypoxic response. Under these conditions, mitochondrial ATP production is less necessary and fermentative glycolysis becomes critical to meet cell energy demands. In this scenario, the more flexible energy metabolism along with an intrinsically activated hypoxic response make these plants better adapted to face several biotic and abiotic stresses.
Keywords: Carbon fixation; Ucp1.; Hypoxic stress; Oxidative stress; Photosynthesis; Stress tolerance